KARAKTERISASI ADSORBEN KOMPOSIT ALUMINIUM OKSIDA PADA LEMPUNG TERAKTIVASI ASAM - Suarya, P. (Jurnal Kimia (Journal of Chemistry); Vol. 6, No. 1 Januari 2012, 2012)
Composite of alluminium oxide in clay has been prepared. The materials were prepared as follow: first, clay was activated with 1.2 M sulphuric acid, then intercalated using polyoxycation of alluminium, and finally calcinated to form composite of alluminium oxide (Al2O3). X-ray diffraction (XRD) was employed to characterize basal spacing (d001). Acid-base titration was used for determining the surface acidity, and spectrophotometer UV-Vis for determining the specific surface area. The results show that activation of clay with sulphuric acid and interchalation with polyoxycation of alluminium increase the surface acidity of aluminium oxide composite in clay the namely. The specific surface area of CC0-0, CCa-0, CCa-1, CCa-2 and Cca-3 were 27.0307 m2/g; 28.2351 m2/g; 29.0040 m2/g; 29.2074 m2/g; and 29.1513 m2/g respectively. The X-ray results indicated that adsorbent was composed by montmorillonite, kaolinite, chlorite, feldspar, and calsite.
Keywords: clay, adsorbent, adsorption, composite of alluminium oxide